THE EFFECT OF FINANCIAL INCENTIVES ON MOTIVATION AND PERFORMANCE OF SALES PERFORMANCE AT PT. HADJI KALLA - firman djamal (Scientia Integritas Utama, 2023)
The purpose of this research was to find out how much influence the provision of financial incentives had on the work motivation and performance of PT. Hadji Kalla, and to find out whether the provision of financial incentives has a direct or indirect effect on the performance of PT. Haji Kalla. This research method uses a quantitative analysis methodology, namely path analysis (path) to find out how much influence the financial incentive variable (X1) has on work motivation (X2) on salesperson performance (Y). The results of this study indicate that the financial incentive variable has a positive and significant effect on work motivation and on the performance of PT. Hadji Kalla and financial incentive variables have an indirect effect on the performance of car salespeople at PT.Hadji Kalla through work motivation.